Increased number of parvovirus B19 infections in southeast Scotland in 2012–2013. (February 2015) - Al Shukri, I.; Hamilton, F.; Evans, M.; Cooper, S.; McKenzie, G.; Willocks, L.; Templeton, K.; Harvala, H.
Abstract: Parvovirus B19 (B19V) infections are a common but under-investigated and under-reported cause of intrauterine infections. An increased number of acute B19V infections was identified in the Edinburgh area in 2012–2013, with 123 infections diagnosed in 33 pregnant women, 76 non-pregnant women and 14 men. All except one pregnant woman were asymptomatic. An overall infection rate of 18% was measured in pregnant women who were tested following B19V exposure (26/141). Furthermore, a 7% seroconversion rate was recorded in non-immune pregnant women who were re-tested after exposure (7/104). A high fetal loss rate (25%; 3/12) was observed in those who had acute B19V infection in early pregnancy (<11 weeks) whereas all pregnancies progressed to term in those where acute infection occurred after a gestational age of 12 weeks. These results suggest that more efforts should be targeted to investigate suspected B19V infections in early pregnancy during epidemic seasons.